Subacute sclerosing panencephalitis mortality, United States, 1979–2016: Vaccine-induced declines in SSPE deaths. Issue 35 (23rd August 2018) - Pallivathucal, Lia B.; Noymer, Andrew
Abstract: Subacute sclerosing panencephalitis (SSPE) is a neurodegenerative disease caused by measles virus. We estimate SSPE age-specific mortality in the United States, 1979–2016. The general decline in SSPE mortality reflects that of measles. Shifts, over time, in SSPE mortality by age echo changes in the age distribution of measles in the 1970s and in the 1989–91 outbreak. The current epidemiological situation is that autochthonous SSPE will disappear in the United States, assuming measles vaccination rates remain high.